Seismic vulnerability of existing buildings: non-invasive approach for dynamic behaviour assessment - Gianluca Acunzo (mediaGEO soc. coop., 2018)
This paper presents a brief overview of the concept of seismic risk, with particular regard to existing civil buildings. Given that the seismic risk can be expressed as a combination involving seismic hazard and seismic vulnerability, these aspects are both discussed, describing the factors that lead to the expected seismic input at the base of a building as well as the ones determining its vulnerability.